Hubungan Pendampingan Persalinan Dengan Lama Persalinan Kala II Di BPS Enok Desa Jarangan Kecamatan Rejoso Kabupaten PasuruanAlimul - Rulita, Aprilian Maya (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2009)
Labouring and delivering are physiologic circle. When labouring, mother start her task to deliver her baby. While medical practitioners tasks are checking the labouring process in order to check the complication. Husband presence is one of the important factors in making the process effective, and the it may also give active role in giving physical and mental support to his wife.The purpose of the study is knowing the relation between labour duration of the second duration in BPS Enak Rejoso in Grati District and pasuruan regency. While the method of this study uses analytic observational design with two research variables: independent variable (labour accompanion) and dependent variable (labour duration of the seon period), and the population of the atudy is all the labour mother in BPS enak rejoso in Grati district and pasuruan regency with the sample of the sampling concecutive sampling technique as 34 people. The data are collected from partograf observation instrumental and checklist and tested with exact fisher test.The result of the study showed that the result of exact fisher test was p = 0,016, which mean that p was bigger than 0,01 and less than 0,05 so that H0 was rejected and H1 was received. It meant that there was a relation between labour accompanion and labour duration of the second period. It happened because of the family role so that the delivery process might run well. It was hoped that family might give more attention on pregnant and labour mother.Key word: labour accompanion, second period of labour.